Development of PLC Festo Module to Support Mechatronics Course in Department of Mechanical Engineering Unesa - Kurniawan, Wahyu Dwi; Soeryanto, Soeryanto; Adiwibowo, Priyo Heru; Arsana, I Made (Proceeding Series of International Conference on Arts and Humanities, 2022)
Equipment assistance in the form of a Festo PLC trainer obtained from Islamic Development Bank (IsDB) has not been optimized to support Mechatronics lectures because there is no module in the operation of the trainer. To answer these problems, the specific purpose of this research is to develop the Festo PLC module to support Mechatronics lectures at the Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Surabaya (Unesa). The long-term goal to be achieved in this research is the realization of learning tools that can bridge the competencies possessed by students with the demands of the rapidly growing needs of the industrial world as an optimal debriefing effort for students who will later work as professionals in industry world. To achieve the above objectives, this research method uses the ADDIE model development (analysis, design, development, implementation, evaluation). The expected result of this research is that the Festo PLC module is declared suitable for use in mechatronics courses and gets a positive response from students so that it can improve their learning outcomes.